On Choosing Between Probability Distributions - Roy, A. D. (Review of Economic Studies, 1954)
Journal Article On Choosing Between Probability Distributions Get access A. D. Roy A. D. Roy Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 3, 1954, Pages 194–202, https://doi.org/10.2307/2295876 Published: 01 January 1954